Young Mania Rating Scale: how to interpret the numbers? Determination of a severity threshold and of the minimal clinically significant difference in the EMBLEM cohort - Lukasiewicz, Michael (Int J Methods Psychiatr Res, 2013)
The aim of this analysis was to identify Young Mania Rating Scale (YMRS) meaningful benchmarks for clinicians (severity threshold, minimal clinically significant difference [MCSD]) using the Clinical Global Impressions Bipolar (CGI‐BP) mania scale, to provide a clinical perspective to randomized clinical trials (RCTs) results. We used the cohort of patients with acute manic/mixed state of bipolar disorders (N = 3459) included in the European Mania in Bipolar Longitudinal Evaluation of Medication (EMBLEM) study. A receiver‐operating characteristic analysis was performed on randomly selected patients to determine the YMRS optimal severity threshold with CGI‐BP mania score ≥ “Markedly ill” defining severity. The MCSD (clinically meaningful change in score relative to one point difference in CGI‐BP mania for outcome measures) of YMRS, was assessed with a linear regression on baseline data. At baseline, YMRS mean score was 26.4 (±9.9), CGI‐BP mania mean score was 4.8 (±1.0) and 61.7% of patients had a score ≥ 5. The optimal YMRS severity threshold of 25 (positive predictive value [PPV] = 83.0%; negative predictive value [NPV] = 66.0%) was determined. In this cohort, a YMRS score of 20 (typical cutoff for RCTs inclusion criteria) corresponds to a PPV of 74.6% and to a NPV of 77.6%, meaning that the majority of patients included would be classified as severely ill. The YMRS minimal clinically significant difference was 6.6 points. Copyright © 2013 John Wiley & Sons, Ltd.